Perancangan Aplikasi Web Bidang Agriculture Berbasis Sistem Pakar Untuk Deteksi Penyakit Cabai Dengan Metode Dempster Shaf - Nunsina Nunsina; Cut Fadhlilah; Mutasar Mutasar (Jurnal Tika, 2023)
Very commonly found in chili plants, but the problem is whether the pest or disease causes significant losses or not. To find out what type of attack occurs on chili plants, sometimes farmers lack knowledge in the field of information on pests and diseases so that there are times when the treatment is not in accordance with the type of attack so the disease continues to spread to other plants. Advances in expert systems can overcome this problem by designing a web-based computer system that is integrated with databases and programming languages such as PHP-MySql so that it can assist farmers in diagnosing the disease that is attacked. The application of an expert system in making decisions uses a forward chaining inference engine (forward reasoning) where cases are traced at the initial state so that goals will be found for the final results of diagnosing chili plant diseases. The results of the implementation of the system, namely the system provides questions in the form of symptoms that must be answered by farmers and the results of this process the system will provide information on what diseases attack plants and solutions for handling them